Effect of different feeding management on the respiratory methane emission and feces-derived methane yield of goat - Sutaryo, Sutaryo; Adiwinarti, Retno; Ward, Alastair James; Kurihara, Mitsunori; Purnomoadi, Agung (Journal of Advanced Veterinary and Animal Research, 2019)
Objective: This study aimed to evaluate the respiratory methane emission and ultimate methane yield (B0) of goat feces that fed roughage consisted of Pennisetum purpureum and Gliricidia) and fed roughage and concentrate with different protein source in the ration (fish meal and soybean meal). Materials and Methods: Fifteen Kacang bucks were allocated to the control group (T0): goats were fed roughage only, T1: goats were fed roughage and concentrate with fish meal as protein sources, and T2: goats were fed roughage and concentrate and the protein source in the ration was soybean meal. Results: The protein content of feces from T0 was significantly lower (p < 0.05) than that from the other treatments. The same phenomenon was also found in the respiratory methane emission in terms of l/head/d, l/kg digestible dry matter, and l/kg body weight. However, there was no significant effect (p > 0.05) of different ration composition on the ultimate methane yield (B0) of goat feces. This study found that B0 of goat feces from treatment T0, T1, and T2 was 17.40%, 25.78%, and 61.29%, respectively, higher than that from the international default value for developing countries. Conclusion: Feeding grass and legume can reduce methane respiration emission in goat. B0 of feces in the present study was higher than that in the international default value; therefore, the potential emission of goat manure in tropical developing countries could be higher than that in the present estimation. J. Adv. Vet. Anim. Res., 6(4): 431-437, December 2019